Marketing Promotion Finance and Accounting System in Banana Chip and Peel Community Micro Business Bandung - Sari, Nur Zeina Maya; Kanya, Nita; Kamil, Indriyati; Nandang, Nandang (LP2M INSURI Ponorogo, 2024)
The banana chip and peel community micro business in Bandung needs help in marketing promotion and financial management despite the high nutritional potential of banana peels. This initiative aims to enhance local micro-businesses' marketing strategies and financial practices by empowering community members with the necessary skills and knowledge. Utilizing a community-based research (CBR) method, the project involved focus group discussions, interviews, and marketing training seminars to identify obstacles and promote product innovation. Participants were taught effective marketing techniques and financial accounting practices, including cash flow management and profit-loss reporting. The results demonstrated a significant improvement in business stability and sales performance, with participants adopting diverse product offerings such as cheese and chocolate-flavored chips. Community engagement played a crucial role, ensuring strategies were culturally relevant and fostering a sense of ownership among participants. In conclusion, this initiative successfully applied theoretical frameworks to enhance the economic viability of local micro-businesses. By integrating effective marketing, sound financial management, and community participation, the program empowered entrepreneurs to innovate and sustain their enterprises, ultimately contributing to the region's economic development. Future efforts should build on these principles to support local businesses further.